Self-Determined to Write: Leveraging Interest, Collaboration, and Self-Direction Through a Journalistic Approach. Issue 5 (3rd September 2019) - Madison, Ed; Anderson, Ross; Bousselot, Tracy
Abstract: Becoming a proficient writer is a core competency for effective communication and central to college and career readiness for learners. Despite broad adoption of more rigorous standards and a push to incorporate writing across the curriculum, the majority of U.S. students across different grade levels fall short of grade-level expectations in writing. This study applies self-determination theory in the design and developmental research of an approach that integrates journalistic interviews and writing practices into typical middle school student English language arts/social studies curricula. In this mixed-methods study, 53 sixth grade students in rural (omitted for review) participated in journalistic learning once per week. The 36-week program applied self-determination theory to build dynamic opportunities for individual interest, collaboration, and self-direction, catalyzing students' self-determined motivation to write. Findings suggest students experienced regular opportunities to learn and apply skills in collaboration and self-direction and were prepared and satisfied learning those skills. On both quantitative and qualitative data, students reported positive perceptions and attitudes, high levels of individual interest and intrinsic motivation to engage and persist in journalistic research and writing, a flow experience in the writing process, high levels of autonomy to be self-directed, competency for critical thinking, and relational support from their teachers and peers as a result of their participation in journalistic learning. Comparing results from the early phase with results at the end, effects all trended in the positive direction with greater exposure and experience in the program.